69‐3: Distinguished Paper: Development of Middle Size Full In‐Cell LCD Module for PC with IGZO. Issue 1 (30th May 2018) - Hata, Masayuki; Tanaka, Kohei; Watanabe, Takuya; Noma, Mikihiro; Tagawa, Akira; Yoshida, Keisuke; Yamamoto, Kaoru; Nagata, Kosuke; Miyazaki, Shinichi; Kitagawa, Daiji
Abstract : We developed the world's first middle size full in‐cell LCD for PC with IGZO technology. We evaluated a new Gate driver In Panel (GIP) structure with latch circuit and confirmed that there were no problems with display and touch panel (TP) performance. Furthermore, we did a feasibility study of higher display resolutions and larger size panels, which showed future possibilities.